Propionibacterium acnes infections in patients with idiopathic scoliosis: a case-control study and review of the literature. (April 2018) - Swarup, I.; Gruskay, J.; Price, M.; Yang, J.; Blanco, J.; Perlman, S.; Widmann, R.
Purpose: Surgical site infection (SSI) caused by Propionibacterium acnes is an infrequent but devastating complication after spinal fusion. The purpose of this study was to identify risk factors for SSI with Propionibacterium acnes after spinal fusion for juvenile and adolescent idiopathic scoliosis (JIS and AIS). Methods: A case-control study was performed. Each case was matched 2:1 for age, gender and diagnosis. Retrospective chart review was performed to obtain relevant demographic, surgical and clinical data for all cases and controls. Statistical analysis included paired t -test and McNemar test, as well as exact logistic regression and robust regression models. Results: This study included ten infection cases (eight AIS, two JIS) and 20 controls (16 AIS, four JIS). In total, six infected cases presented within two weeks of the index procedure (acute infection) and four infected cases presented more than one year from the index procedure (delayed infection). The most common presentation for acute infections was wound drainage, while back pain was more common in delayed infections. All infections were successfully treated with surgical irrigation and debridement and postoperative antibiotics. Hardware was removed for patients with delayed infections. The strongest risk factor for infection was increased requirement for blood transfusion, but it did not reach statistical significance. Conclusion: SSI with Propionibacterium acnes is an important complication after spinal fusion for idiopathic scoliosis. These infections can be successfully treated, but larger studies are needed to further identify risk factors and establish standardized guidelines for the treatment and prevention of this complication. Level of Evidence Level III: